O assédio moral virtual na perspectiva dos técnicos administrativos em educação de uma instituição pública de ensino - Nunes, Jesner (2024)
This master's dissertation aims to identify and analyze the practices of virtual bullying in the workplace and the coping strategies used to mitigate this phenomenon, from the perception of the Administrative Technicians in Education at UFSM. To this end, a quantitative research was carried out with 136 UFSM employees based on the Labor Scales of Moral Harassment (ELAM), adapted to the context of virtual moral harassment. One of the main findings of this study was the finding that there is a group of sectors (PROGRAD; PRPGP and PRE) with a higher probability of being suffering violations of practices related to virtual moral harassment, which generates serious consequences not only for the victims, but also for the organizational environment as a whole. Among the impacts mentioned by the respondents, the obligation to use digital systems such as WhatsApp and others stand out, in addition to the need to meet goals that are almost impossible to achieve, in the same sense, the receipt of confusing information by digital means and the obligation to do work against one's will using digital devices were highlighted. The study seeks to contribute to the understanding of virtual bullying in the public educational context, proposing coping strategies and promoting a healthier and more ethical work environment